2016
DOI: 10.1590/0102-6720201600010009
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Pre and Postoperative Upper Digestive Endoscopy in Patients Who Underwent Roux-en-Y Gastrojejunal Bypass

Abstract: Background:Bariatric operations have variable range of complications and postoperative benefits. Gastroesophageal reflux is considered potential factor that may result in damage to the esophageal mucosa and this subject is quite controversial in the literature. Aim : To evaluate patients who underwent to Roux-en-Y gastrojejunal bypass correlating epidemiologic and endoscopic findings in pre and postoperative periods. Method : A retrospective, paired study which evaluated 110 patients. Inclusion criteria were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…Considering the possible endoscopic alterations found in the UGE on patients undergoing bariatric surgery, research suggests a classification of endoscopic findings in the preoperative RYGB, reinforcing the importance of preoperative screening 5 .…”
Section: Discussionmentioning
confidence: 98%
“…Considering the possible endoscopic alterations found in the UGE on patients undergoing bariatric surgery, research suggests a classification of endoscopic findings in the preoperative RYGB, reinforcing the importance of preoperative screening 5 .…”
Section: Discussionmentioning
confidence: 98%
“…[8,10] this may raise a question about the relation between obesity and chronic gastritis. A study by Clapp [13] found that chronic gastritis was present in 44% of patients and this percent was reduced after the operation, even in patients who underwent Roux-en-Y Gastric bypass Czeczko et al [14] found that chronic gastritis decreased to a lower extent after the operation.…”
Section: Discussion:-mentioning
confidence: 99%
“…(eight patients, 16%, including 2% with a marginal ulcer) (13) . A recent study presented stenosis as the main finding in 35.5% of patients, with marginal ulcer being the second most common finding (n=9) (7) . In another series associating symptoms to specific findings, reports included normal surgical anatomy (31.6%), anastomotic stricture (52.6%), marginal ulcer (15.8%), unraveled non-absorbable sutures causing functional obstruction (4%) and gastro-gastric fistula (2.6%) (10) .…”
Section: Participantsmentioning
confidence: 95%